No Bilingual Benefits Despite Relations Between Language Switching and Task Switching - Timmermeister, Mona; Leseman, Paul; Wijnen, Frank; Blom, Elma (Frontiers in Psychology, 2020)
Previous research has shown that bilingual children outperform monolinguals on tasks testing cognitive control. Bilinguals’ enhanced cognitive control is thought to be caused by the necessity to exert more language control in bilingual compared to monolingual settings. Surprisingly, between-group research of cognitive effects of bilingualism is hardly ever combined with within-group research that investigates relationships between language control and cognitive control. The present study compared 27 monolingual Dutch and 27 bilingual Turkish-Dutch children matched on age and fluid intelligence on their performance in a nonverbal switching task. Within the group of bilinguals, the relationship between nonverbal switching and language switching was examined. The results revealed no between-group differences on nonverbal switching. Within the bilingual sample, response times in the language switching and nonverbal switching tasks were related, although no relationships were found between accuracy, switch cost and mixing cost on both tasks. The results support the hypothesis that children utilize domain-general cognitive control in language switching, but this relationship does not entail that bilinguals have better cognitive control than monolinguals.